Colon cancer as tow histopathological and molecular different type of cancer such as right and left - Zahedi, Mahlagha; Moghimi, Mansour; Yazdinejad, Mahdi (Revista Publicando, 2018)
Background: Colon cancer is the second common cancer among men and the third among women, histopathological categories for anatomical assessment of colorectal carcinoma has not been defined properly. However, considering colon embryonic origination from mid- and hindgut, suggests the idea that there is histological and molecular differences between these two parts. Material & Method: From March, 2005 up to March, 2015, two hundred and ninety-one patient underwent curative surgery were included. Cases were studied for their age, gender, tumor location, site of tumor metastasis, tumor TNM classification, k-ras marker status and survival. Result: Right sided colon cancers were 100 cases and left sided were 129. Most of the patients with right sided cancers were young and female. Right sided tumors were significantly larger in size, presenting in higher grades than left sided tumors. However, the stages were the same in both sides. Right sided tumors K-ras mutant expression was approximately 1.5 times more than the left. Patients suffering from a right sided colon cancer had a less survival rate (RCC=22%, LCC=31.78%, P-value=0.001). Conclusion: It seems that there is clinical, histopathologic, and molecular difference between right and left sided colon tumors that they can be categorized in two separate groups. In our study, right sided tumors have more unfavorable characteristics rather than left sided ones. So, involved side (right side of tumor), older ages and stage of the tumor (higher stages) might be considered as independent poor prognostic factors of colorectal carcinoma.